Diastolic strain time as predictor for systolic dysfunction among patients with active breast cancer. Issue 11 (20th July 2020) - Hochstadt, Aviram; Arnold, Joshua; Rosen, Roni; Sherez, Chen; Sherez, Jack; Mor, Liat; Derakhshesh, Matthew; Moshkovits, Yonatan; Merdler, Ilan; Arbel, Yaron; Kapusta, Livia; Rozenbaum, Zach; et al.
Abstract: Background: Although diastolic dysfunction is common among patients treated with cancer therapy, no clear evidence has been shown that it predicts systolic dysfunction. This study evaluated the correlation of diastolic strain time (Dst) with the routine echocardiography diastolic parameters and estimated its role in the early detection of cardiotoxicity among patients with active breast cancer. Methods: Data were collected as part of the Israel Cardio‐Oncology Registry (ICOR), a prospective registry enrolling all adult patients referred to the cardio‐oncology clinic. All patients with breast cancer, planned for Doxorubicin therapy, were included. Echocardiography, including global longitudinal systolic strain (GLS) and Dst, was assessed at baseline before chemotherapy (T1), during Doxorubicin therapy (T2) and after the completion of Doxorubicin therapy (T3). Cardiotoxicity was determined by GLS relative reduction of ≥15%. Dst was assessed as the time measured (ms) of the myocardium lengthening during diastole. Results: Among 69 patients, 67 (97.1%) were females with a mean age of 52 ± 13 years. Dst was significantly associated with the routine diastolic parameters. Significant GLS reduction was observed in 10 (20%) patients at T3. Both in a univariate and a multivariate analyses, the change in Ds basal time from T1 to T2 emerged to be significantly associated with GLS reduction at T3 ( P < .04). Conclusions: Among breast cancer patients, Dst showed high correlation to the routine diastolic echocardiography parameters. Change in Ds basal time emerged associated with clinically significant systolic dysfunction as measured by GLS reduction.